Redox mediation at poly(o-aminophenol) coated electrodes: mechanistic diagnosis from steady state polarization curves - Gabriel Ybarra; Carlos Moina; María Inés Florit; Dionisio Posadas (Journal of Electrochemical Science and Engineering, 2018)
In this work, the mediated reduction of Fe(CN)63- and Fe3+ in poly(o-aminophenol) coated electrodes is analyzed by means of a diagnosis diagram based on the features of the steady state current-potential curves. This analysis allows to identify the current determining process and to reproduce the experimental characteristics of the polarization curve from the relevant kinetic and thermodynamic parameters with a minimum amount of experimental measurements.